The impact of low-intensity blood flow restriction endurance training on aerobic capacity, hemodynamics, and arterial stiffness - Karabulut, M.; Esparza, B.; Dowllah, I. M.; Karabulut, U. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to determine the effects of short-term low-intensity blood flow restriction (BFR) endurance training (ET) programs on measures of aerobic capacity, hemodynamics, and arterial stiffness in healthy young males. METHODS: Thirty-nine healthy young recreationally active males participated in this short-term training study. They were randomly assigned to a high-intensity (HI; N.=11; trained at 60-70% of VO2 reserve [VO2R]), low-intensity (LI; N.=8; trained at 30-40% of VO2R), low-intensity with BFR (LI-BFR; N.=10; trained at 30-40% of VO2R with BFR) or a non-exercising control group (N.=10). The exercising subjects completed a 6-wk training protocol on a treadmill. Assessment of aerobic capacity (VO2max), hemodynamics and arterial stiffness were done before and after training. RESULTS: Statistical analyses revealed a significant condition main effect (P<0.05) for VO2max, indicating significant increase (P<0.05) in VO2max in LI-BFR group compared to control. There were no significant changes for resting heart rate (RHR), systolic blood pressure (SBP), diastolic blood pressure (DBP), carotid-radial pulse wave velocity (PWV), and carotid-femoral PWV (P>0.05). However, femoral-tibial PWV decreased significantly (P<0.05) from baseline to post-training. CONCLUSIONS: The results indicate that the application of BFR during ET may cause faster and/or greater adaptations in one or more physiological systems resulting in improved cardiorespiratory fitness.